Placing greater emphasis on vocational education in Kenya - Erima, Gloria E (Open Science Journal, 2021)
Kenya, like other countries in the Sub Sahara Africa (SSA), Technical, vocational education, and training (TVET) is believed to be an obvious remedy to youth employment across the region. As we view TVET in this way, the perception in many if not all the countries across SSA is that TVET is a salvation for the intellectually incapable or those with less or no aspiration for better paying jobs. For the elite and middle class, TVET is in reality not for their children, as it seems almost ‘useless’. Interestingly, even with such perceptions, Kenya and other SSA countries have continued to ‘embrace’ TVET in their education systems but with little investment towards those TVET programmes. In 2018, there was a shift in policy in Kenya with TVET receiving more attention, and as a result attracting a larger budget allocation. The government slashed fees for students in technical and vocational education institutions, and raised public funding in its latest bid to grow the critical skills base needed to achieve the country’s economic ambitions. To support this policy, the government agreed to give an annual bursary of US300 for every student who joins the technical institutions (University World News, 2018). The students will access the funding through the Higher Education Loans Board (HELB), the agency that disburses loans to university students on behalf of the government. This policy comes as a result of the World bank warning regarding a widening disconnect between labour market skills needs and the graduates of higher education institutions. This paper provides an overview of the state of TVET in Kenya, challenges and possible recommendations to support the new TVET reforms towards making it more attractive for learners in Kenya.